Unobtrusive Health Screening on an Intelligent Toilet Seat - T. Schlebusch (Acta Polytechnica, 2011)
Home monitoring is a promising way to improve the quality of medical care in an ageing society. To circumvent the problem that especially demented patients may forget or be stressed by the use of medical devices at home, monitoring devices should be embedded in objects of daily life to check the patient’s health status whenever possible, without any interaction with the patient him/herself. This paper presents an intelligent toilet performing an unobtrusive health check when a person sits down. A variety of physical, electro-physical and urine parameters are analysed. This paper takes electrocardiogram and bioimpedance spectroscopy measurements and shows the practicability of measuring them on a toilet seat.